The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.jrmge.2015.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Strength properties of soft clay treated with mixture of nano-SiO2 and recycled polyester fiber

Abstract: Please cite this article as: Changizi F, Haddad A, Strength properties of soft clay treated with mixture of nano-SiO 2 and recycled polyester fiber, Abstract: This paper investigates the effect of recycled polyester fiber, produced from polyethylene (PET) bottles, in combination with nano-SiO2 as a new stabilizer to improve the mechanical properties of soils. We intend to study the effect of adding nano-SiO2 and recycled polyester fiber on soil engineering properties, especially the shear strength and unconfin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(40 citation statements)
references
References 16 publications
(14 reference statements)
1
37
0
2
Order By: Relevance
“…One method of using plastic for soil stabilisation is to use the plastic in the form of discrete fibres (Yetimoglu and Salbas 2003), because when plastic materials are merged with soils, they behave similar to fibre-reinforced soil. Several researches have been conducted to investigate the effectiveness of plastic waste materials in the form of discrete fibres on properties of soils (Ziegler et al 1998;Babu and Chouksey 2011;Mondal 2012;Ahmadinia et al 2012;Modarres and Hamedi 2014;Fauzi et al 2015;Changizi and Haddad 2015;Rawat and Kumar 2016;Peddaiah et al 2018;Salimi and Ghzavi 2019). These researchers found that using plastic waste materials for soil stabilisation will improve the properties of weak soils such as an increase in UCS, CBR, and Mr and a decrease in the soil plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…One method of using plastic for soil stabilisation is to use the plastic in the form of discrete fibres (Yetimoglu and Salbas 2003), because when plastic materials are merged with soils, they behave similar to fibre-reinforced soil. Several researches have been conducted to investigate the effectiveness of plastic waste materials in the form of discrete fibres on properties of soils (Ziegler et al 1998;Babu and Chouksey 2011;Mondal 2012;Ahmadinia et al 2012;Modarres and Hamedi 2014;Fauzi et al 2015;Changizi and Haddad 2015;Rawat and Kumar 2016;Peddaiah et al 2018;Salimi and Ghzavi 2019). These researchers found that using plastic waste materials for soil stabilisation will improve the properties of weak soils such as an increase in UCS, CBR, and Mr and a decrease in the soil plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Since soil samples grouted with CS will improve compressive strength, CS-soil mixtures should also obtain a higher shear strength compared with pure soil samples. Changizi and Haddad (2015) added 0.5%, 0.7% and 1% CS to soil to discover the mechanical enhancing effect. They found that both the friction angle and cohesion were enhanced for grouted soils [58].…”
Section: Mechanical Properties Of Cs-soil Mixturesmentioning
confidence: 99%
“…Changizi and Haddad (2015) added 0.5%, 0.7% and 1% CS to soil to discover the mechanical enhancing effect. They found that both the friction angle and cohesion were enhanced for grouted soils [58]. Besides, the relationship between the shear stress ratio (the ratio of shear stress to effective vertical stress) and shear displacement was investigated for a pure sand sample, a 1-week-cured CS-sand sample, and a 4-week-cured CS-sand sample, as shown in Figure 9 [50].…”
Section: Mechanical Properties Of Cs-soil Mixturesmentioning
confidence: 99%
“…Silica nanostabilizer hold promising prospective material for weak soil stabilization on account of cost-effectiveness, high durability characteristics, and reliable stabilization 2224 . In this connection, few reports have investigated the influence of silica nanoparticles (NPs) on the geotechnical properties of different form of stabilized soils 21,24,25 . To the best of our knowledge, no study has found in the literature concerning the effect of plant-mediated nanosilica additive on subgrade soil for railway construction purpose.…”
Section: Introductionmentioning
confidence: 99%